The Performance of Private Unit Trusts in Malaysia - Pang, Looi Fai (1998)
As investments in the Malaysian capital market become institutionalised, unit trusts are increasingly becoming the main vehicle for a retail investor to participate in the capital market. Unit Trusts are originally promoted to generate stable income with reasonable risks for medium to long term investors. This study examines the performance of 27 unit trusts in Malaysia.Monthly data were collected over a 8 year period from 1990 to 1997. Performance is measured by the returns earned by the Unit Trust. However these returns must commensurate with the level of risk and therefore risk-adjusted performance measures are used . Performance evaluation is further refined by investigating the ability of the Unit Trust manager to select correct investments at the right time i.e. his/her timing and selection performance. The general findings of this study indicate that most Malaysian Unit Trusts generally under perform the market, are poorly diversified and generate low levels of returns, of the 27 funds studied only 33% outperformed the market. However after adjusting for different risk levels, none of the funds were able to outperform the market. The average R2 was 0.516 indicating most funds were not fully diversified. Specifically most funds analysed attained half the level of diversification compared to the market portfolio which is used as the benchmark portfolio The findings indicate that funds generally perform better during a bear market as compared to a bull market. Though the returns for unit trusts in a down trending period was negative, the losses were less than the market portfolio, whereas in an uptrend period the returns of unit trusts were less than the market return. The findings also indicate that the timing and selection ability of Unit Trust managers were poor with all funds having negative net selection. Timing ability was only marginally positive for income growth funds. This implies that in terms of the performance measured on the basis of returns per unit of risk and the level of diversification achieved by these funds, it would have been better for investors to invest on their own.